2015
DOI: 10.1007/s13142-015-0382-4
|View full text |Cite
|
Sign up to set email alerts
|

Interest in a Twitter-delivered weight loss program among women of childbearing age

Abstract: Weight management through the childbearing years is important, yet few women have access to efficacious weight loss programs. Online social network-delivered programs may increase reach and thus impact. The aim of this study was to gauge interest in a Twitter-based weight loss intervention among women of childbearing age and the feasibility of recruitment via Twitter. We recruited English-speaking women aged 18-45 years (N = 63) from Twitter to complete an anonymous online survey including open-ended questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…design, engaging content provided) or personal factors, such as interest in the intervention itself or the stage of change of the individual. Social media use differs by age in general [ 55 ], and in formative research examining interest in a Twitter-delivered weight loss intervention, Waring et al [ 56 ] found that the youngest group of women included in their study were the least likely to be interested in a Twitter-delivered weight loss intervention; 62% in 21–29 years, 96% in 30–34 years and 77% in 35–45 years.…”
Section: Discussionmentioning
confidence: 99%
“…design, engaging content provided) or personal factors, such as interest in the intervention itself or the stage of change of the individual. Social media use differs by age in general [ 55 ], and in formative research examining interest in a Twitter-delivered weight loss intervention, Waring et al [ 56 ] found that the youngest group of women included in their study were the least likely to be interested in a Twitter-delivered weight loss intervention; 62% in 21–29 years, 96% in 30–34 years and 77% in 35–45 years.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Waring and colleagues surveyed 63 overweight or obese women of childbearing age who were Twitter users to find out if they had an interest in participating in a weight-loss intervention delivered via Twitter. The majority (81%), but not all, were at least somewhat interested in such a program [ 92 ]. Further research is needed to explore which populations are most interested in this type of intervention.…”
Section: Future Researchmentioning
confidence: 99%
“…Compared with offline friends, family members, and Facebook friends, participants who use Twitter to discuss their weight loss are exposed to more sources of positive social influence and fewer sources of negative social influence regarding weight loss [ 20 ]. Women of childbearing age actively use Twitter and show great interest in Twitter-based weight loss interventions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%